On the neutrality of socially responsible investing - Lutz G. Arnold (Theoretical Economics, 2023)
This paper investigates the conditions under which socially responsible investment (SRI) is neutral from the viewpoint of general equilibrium theory. Three conditions are jointly sufficient for neutrality of SRI. First, the financial market is complete and SRI does not compromise the spanning opportunities it provides. Second, consumers' rankings of consumption bundles are unaffected by their asset holdings. Third, firms maximize shareholder value. Under an additional assumption that is satisfied, e.g., if SRI takes the form of negative screening, the taxes and transfers needed to implement a Pareto-optimal allocation are the same as in the absence of SRI. SRI is neutral despite financial market incompleteness if there are perfect substitutes for targeted stocks.
Keywords: D51; D52; D53; G13; M14; 330; general equilibrium; market incompleteness; Socially responsible investing